2020
DOI: 10.1090/tran/8040
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of random perturbations of Toeplitz matrices with finite symbols

Abstract: Consider an N × N Toeplitz matrix T N with symbol a(λ) := d 1 =−d 2 a λ , perturbed by an additive noise matrix N −γ E N , where the entries of E N are centered i.i.d. complex random variables of unit variance and γ > 1/2. It is known that the empirical measure of eigenvalues of the perturbed matrix converges weakly, as N → ∞, to the law of a(U ), where U is distributed uniformly on S 1 . In this paper, we consider the outliers, i.e. eigenvalues that are at a positive (N -independent) distance from a(S 1 ). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 37 publications
(90 reference statements)
1
13
1
Order By: Relevance
“…The choice of γ in each of the three cases given in Corollary 1.8 is so that (1.11) is satisfied. Theorem 1.7 and its corollary are similar to several recent works concerning fixed matrices perturbed by random matrices [7,8,10,29,60,61,62,73]. The case when E contains independent Gaussian entires was investigated in [7,29,60,61,62].…”
Section: 14)supporting
confidence: 58%
“…The choice of γ in each of the three cases given in Corollary 1.8 is so that (1.11) is satisfied. Theorem 1.7 and its corollary are similar to several recent works concerning fixed matrices perturbed by random matrices [7,8,10,29,60,61,62,73]. The case when E contains independent Gaussian entires was investigated in [7,29,60,61,62].…”
Section: 14)supporting
confidence: 58%
“…It is immediate by Definitions 2.3 and 2.4 that the ESD of a random matrix polynomial coincides with the ESD of its (random) companion matrix (3). Indeed, in this paper we will strongly rely on its equivalence.…”
Section: Empirical Spectral Distributionsmentioning
confidence: 98%
“…In Sect. 3, we obtain our first main result: the almost sure limit, for n → ∞, of the empirical spectral distribution of a random n × n monic complex Gaussian matrix polynomial of degree k. In Sect. 4, our second main result is discussed: the almost sure limit, for k → ∞, of the empirical spectral distribution of a random n × n monic complex Gaussian matrix polynomial of degree k. In Sect.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the noncentered case, Davies and Hager [15] showed that if A is a Jordan block and h n for some appropriate , then almost all of the eigenvalues of A g G n lie near a circle of radius 1=n with probability 1 o n .1/. Basak, Paquette, and Zeitouni [4,5] showed that for a sequence of banded Toeplitz matrices A n with a finite symbol, the spectral measures of A n gn G n converge weakly in probability, as n 3 I, to a predictable density determined by the symbol. Both of the above results were recently and substantially improved by Sjöstrand and Vogel [37,38], who proved that for any Toeplitz A, almost all of the eigenvalues of A g n G n are close to the symbol curve of A with exponentially good probability in n. Note that none of the results mentioned in this paragraph explicitly discuss the .…”
Section: Related Workmentioning
confidence: 99%